Investigation of the pore blockage of a Brazilian dolomite during the sulfation reaction - Avila, Ivonete; Crnkovic, Paula M. [UNESP]; Milioli, Fernando E.; Luo, Kai H. (Elsevier B.V., 2012)
The influence of the temperature and reaction time on the sulfation process of a dolomite is investigated in this paper. The sulfation effectiveness was evaluated and correlated with changes in the physical characteristics of a Brazilian dolomite during the reactive process. Calcination and sulfation experiments were performed under isothermal conditions for dolomite samples with average particle sizes of 545 mu m at temperatures of 750 degrees C, 850 degrees C and 950 degrees C at different times of sulfation. Thermogravimetric tests were applied to establish the reactivity variation of the dolomite in function of the time in the sulfation reaction and evaluate the methodology of the samples preparation. Porosimetry tests were performed to study the pore blockage of dolomite during the sulfation reaction. The highest values of BET surface area were 25.55 m(2)/g, 29.55 m(2)/g and 12.62 m(2)/g for calcined samples and after their sulfation processes, conversions of 51.5%, 61.9% and 42.8% were obtained at 750 degrees C, 850 degrees C and 950 degrees C, respectively. Considering the process as a whole, the best fit was provided by a first-order exponential decay equation. Moreover, the results have shown that it is possible to quantify the decreasing in the dolomite reactivity for sulfur dioxide sorption and understand the changes in the behavior of the sulfation process of limestones when applied to technologies, as fluidized bed combustor, in which sulfur dioxide is present. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Pore blockage; Dolomite; Sulfation; Thermal decomposition; BET surface area